ISLAMIC SCHOOL IMAGE AND SERVICE QUALITY ON ISLAMIC ELEMENTARY SCHOOLS: THE ROLE OF WORD OF MOUTH AS MEDIATION - Hamzah, Hamzah; Syarif, Miftah; Purwati, Astri Ayu; Sudarno, Sudarno (Jurnal Aplikasi Manajemen, 2023)
In the current era, schools founded by private parties are increasing. Of course, it increases the competition between these private and public schools. Schools with international concepts, for example, have also become many choices for prospective students. Besides that, religion-based schools such as Christian, Buddhist, or Islamic schools are also an option now. For this reason, this study aimed to analyze the role of school Islamic image, service quality, and word of mouth on parents' decisions to choose private Islamic schools in Pekanbaru. This type of research is quantitative research. This study used 200 parents of grade 1 students at a private Islamic elementary school in Pekanbaru as samples, and the sampling technique used was simple random sampling. A structural equation model (SEM) with PLS is the data analysis technique. The results of this study indicate that Islamic school image has no significant influence on word of mouth, Islamic school image has no significant influence on parents' interest, Service quality has an impact on word of mouth, Service quality has an influence on parents' interest, Word of mouth can't mediate the relationship of Islamic school image on parent's interest, and Word of mouth can mediate the relationship service quality on parent's interest. Therefore, the Islamic idea does not motivate parents to choose their children's schools. Still, the service quality is the key to increasing their competitiveness against other private schools.